2017
DOI: 10.1159/000480038
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Inadequacy of the Placebo Model and the Development of an Alternative Conceptual Framework

Abstract: Placebo effects are often attributed to clinical interactions and contextual factors that affect expectations of the patient about the treatment and result in symptom changes. The prevailing conceptualization consists of an undifferentiated placebo response that needs to be minimized in controlled investigations and maximized in clinical practice. However, treatment outcome is the cumulative result of the interaction of several classes of variables with a selected treatment: living conditions (housing, nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 55 publications
2
101
0
Order By: Relevance
“…In line with recent recommendations [70], deteriorations with respect to the primary behavioral outcome were explored. Visual inspection of self-reported anxiety measures before and after EXP training suggested that 5 out of 23 subjects displayed a numerical increase in anxiety while 9 subjects displayed a numerical anxiety increase following the SHC training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with recent recommendations [70], deteriorations with respect to the primary behavioral outcome were explored. Visual inspection of self-reported anxiety measures before and after EXP training suggested that 5 out of 23 subjects displayed a numerical increase in anxiety while 9 subjects displayed a numerical anxiety increase following the SHC training.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the proportion did not differ between the EXP and the SHC training arguing against specific effects of amygdala- vlPFC connectivity training. The outcome of an intervention is influenced by multiple factors [70], including pretreatment individual differences. The identification of markers that predict treatment response [83] and the use of repeated training sessions may increase the number of participants that respond to rt-fMRI NFTs.…”
Section: Discussionmentioning
confidence: 99%
“…1), where all may contribute to the presentation of a clinical condition. These pathways include biological, psychological, and social factors of iatrogenic nature, whose consequences (syndromes, symptoms and any sort of problem) may be considered as potentially counter-therapeutic [72]. …”
Section: Assessing Iatrogenic Psychopathologymentioning
confidence: 99%
“…During the follow-up period, 3 participants attempted suicide in the relaxation group versus 1 patient in the ACT group. In order to address multifactorial ingredients of treatment outcome [23], description of patients having attempted suicide during the study period are available in the supplementary material.…”
Section: Resultsmentioning
confidence: 99%